Detection of lead and cadmium pollution in Tigris River, water stations, and tap water in Baghdad Governorate (Experimental and Applied Veterinary Research Journal, 2025)
Background: Heavy metals such as cadmium (Cd) and lead (Pb) are among the most hazardous environmental pollutants because of their toxic effects on humans and other living organisms, even at low concentrations. This study aimed to assess the levels of Cd and Pb contamination in different water sources across Baghdad Governorate, including river water, water treatment plants, and tap water. Methodology: This study was conducted between February 2023 and January 2024. A total of 1,296 water samples were collected from six locations, and Cd and Pb concentrations were determined. Results: Elevated concentrations of Cd and Pb were detected across all water sources. The highest mean of Pb concentration was recorded in river water (0.059 mg/L), followed by tap water (0.052 mg/L) and treated water (0.043 mg/L), all of which exceeded the WHO safety limit of 0.01 mg/L. Similarly, Cd concentrations were highest in river water (0.026 mg/L), followed by tap water (0.044 mg/L) and treated water (0.036 mg/L), surpassing the WHO guideline of 0.003 mg/L. Seasonal variations showed that Cd concentrations were the highest in summer, whereas Pb levels were the highest in spring. Conclusions: The prevalence of Cd and Pb contamination varied by water source and location. Cd pollution was nearly six times more likely to exceed permissible limits compared to Pb (P < 0.0001). Moreover, seasonal differences were evident, with Cd exceeding Pb in summer, while Pb surpassed Cd in spring.